2017
DOI: 10.1146/annurev-physiol-021115-105447
|View full text |Cite
|
Sign up to set email alerts
|

Trefoil Factor Peptides and Gastrointestinal Function

Abstract: Trefoil factor (TFF) peptides, containing a 40-amino acid motif, including six conserved cysteine residues that form intramolecular disulfide bonds, are a family of mucin-associated secretory molecules mediating many physiological roles that maintain and restore gastrointestinal (GI) mucosal homeostasis. TFF peptides play important roles in response to GI mucosal injury and inflammation. In response to acute GI mucosal injury, TFF peptides accelerate cell migration to seal the damaged area from luminal content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
123
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(143 citation statements)
references
References 157 publications
(277 reference statements)
3
123
0
5
Order By: Relevance
“…They are stable secretory proteins widely expressed in the gastrointestinal mucosa, and their role in the protection and repair of epithelial surfaces has been confirmed (Kjellev, ). In response to acute mucosal injury, TFFs accelerate cell migration to seal the damaged area from luminal contents, whereas chronic inflammation leads to increased TFF expression to prevent further progression of the disease (Aihara, Engevik, & Montrose, ). An immunohistochemistry study on colorectal biopsy specimens found that TFF1 was expressed in severe UC patients, whereas no expression was detected in normal tissue (Longman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…They are stable secretory proteins widely expressed in the gastrointestinal mucosa, and their role in the protection and repair of epithelial surfaces has been confirmed (Kjellev, ). In response to acute mucosal injury, TFFs accelerate cell migration to seal the damaged area from luminal contents, whereas chronic inflammation leads to increased TFF expression to prevent further progression of the disease (Aihara, Engevik, & Montrose, ). An immunohistochemistry study on colorectal biopsy specimens found that TFF1 was expressed in severe UC patients, whereas no expression was detected in normal tissue (Longman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…TFF1 protects the gastrointestinal mucosa from damage and repairs it through cell migration after injury. TFF3 promotes normal cell migration and maintains gastrointestinal mucosal integrity . Studies focused on gastric cancer have identified a cancer suppressor function in TFF1 and effects that promote cancer development in TFF3.…”
Section: Discussionmentioning
confidence: 99%
“…The trefoil factor family peptides (TFFs) are a family of three thermostable, protease‐resistant polypeptides secreted chiefly from the mucus‐secreting cells of the gastrointestinal tract: TFF1, TFF2, and TFF3 . TFF1 is mainly expressed in the fundus and antrum of gastric mucous cells; TFF2, in mucous neck cells of fundic glands and basal cells of antral and pyloric glands; TFF3, in goblet cells in normal gastric tissue . All three take part in the carcinogenesis of gastric cancer .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…рис.3). Келихоподібні клітини, тип спеціалізованих епітеліоцитів, які відіграють захисну роль у кишечнику, завдяки продукції біоактивних компонентів, що включають в себе муцини, кишечні фактори (trefoil factors) та інші про-тимікробні субстанції [13], сприяє цілісності кишкового бар'єра та забезпечує гомеостаз здорової кишки [14]. Дослідженнями остан-ніх років було показано, що окрім захисної функції, келихоподібні клітини епітелію тон-кої кишки можуть виконувати транспортну, утворюючи goblet cells associated-antigen passages (GCPs-канали) для проникнення водорозчинних невеликих речовин з прос-віту кишки до дендритних клітин у lamina propria [15].…”
Section: результати та їх обговоренняunclassified